A novel Streptococcus species causing clinical mastitis in a pregnant donkey. (September 2021) - Podico, Giorgia; Gray, Sarah M.; Wang, Leyi; Canisso, Igor F.
An 8-y-old jenny was presented because of anorexia and mild depression. The jenny had weaned her colt 10 d before the admission. Upon arrival at the University of Illinois Veterinary Teaching Hospital, the heart rate was elevated, and the right udder was painful and swollen on palpation. Milk stripping of the affected side revealed purulent content; the contralateral udder had normal-appearing milk. Cytology of mammary gland secretions from the affected side revealed a large number of hypersegmented reactive neutrophils with phagocytized bacteria. Complete blood count, serum chemistry, and fibrinogen were within normal limits. A diagnosis of clinical mastitis was made, and the jenny was started on a 5-d course of broad-spectrum antibiotics, a non-steroidal anti-inflammatory, hydrotherapy, and milk stripping. Clinical signs reduced over time, and the cure was attained by 96 h post-admission. Aerobic culture and subsequent MALDI-TOF MS analysis identified a bacterium of the Streptococcus genus but not the species. Whole-genome analysis was performed, and 16S rDNA sequencing and analysis determined that our isolate 20-37394 clustered with 2 other Streptococcus strains (27284-01 and 28462). Single-nucleotide variations and phylogenetic tree analysis revealed that Streptococcus 20-37394 had 96.8% and 94.9% identities to Streptococcus strains 27284-01 and 28462, respectively; therefore, the bacteria isolated in our case was deemed as a new Streptococcus species.